2016
DOI: 10.5051/jpis.2016.46.6.415
|View full text |Cite
|
Sign up to set email alerts
|

The hidden X suture: a technical note on a novel suture technique for alveolar ridge preservation

Abstract: PurposeThe present study investigated the impact of 2 different suture techniques, the conventional crossed mattress suture (X suture) and the novel hidden X suture, for alveolar ridge preservation (ARP) with an open healing approach.MethodsThis study was a prospective randomized controlled clinical trial. Fourteen patients requiring extraction of the maxillary or mandibular posterior teeth were enrolled and allocated into 2 groups. After extraction, demineralized bovine bone matrix mixed with 10% collagen (DB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…BMI results were significantly decreased in hemodialysis patients compared to healthy controls, suggesting that patients with low BMI are at high risk of morbidity. These findings are in line with previous studies, which demonstrated that increased BMI is associated with better survival, whereas low BMI and weight loss are associated with increased mortality (the so-called obesity paradox) [ 14 , 15 ]. Both cardiovascular biomarkers (hs-TnT and CK-MB) were significantly higher in hemodialysis patients than in healthy controls.…”
Section: Discussionsupporting
confidence: 92%
“…BMI results were significantly decreased in hemodialysis patients compared to healthy controls, suggesting that patients with low BMI are at high risk of morbidity. These findings are in line with previous studies, which demonstrated that increased BMI is associated with better survival, whereas low BMI and weight loss are associated with increased mortality (the so-called obesity paradox) [ 14 , 15 ]. Both cardiovascular biomarkers (hs-TnT and CK-MB) were significantly higher in hemodialysis patients than in healthy controls.…”
Section: Discussionsupporting
confidence: 92%
“…Some of the subjects had X sutures, while others received hidden X sutures. In the previous study by the current authors, Hidden X sutures have been proven to be advantageous for counteracting alveolar ridge resorption and preserving more width of the keratinized tissue [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The ‘up’ sides of all the membranes were laid facing the occlusal plane. The membrane was held in place by suture thread (Ethilon 4-0, Ethicon, Cincinnati, OH, USA), using hidden X sutures [ 16 ] or X sutures, and secondary healing was obtained. No efforts were made to obtain primary closure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reasons for tooth extraction were periodontal lesions, dental caries, or fracture. Each residual extraction socket involved bone loss of less than 50% in all dimensions [ 21 ]. The exclusion criteria were pregnancy or lactation, a history of radiotherapy or chemotherapy for a malignancy in the past 5 years, autoimmune diseases, allergy to collagen, a history of systemic diseases that would contraindicate surgical treatment, long-term nonsteroidal anti-inflammatory drug therapy, requiring antibiotic prophylaxis, heavy smoking (>10 cigarettes per day), uncontrolled or untreated periodontal disease, and inability to provide consent for participation in the study or to accept the proposed treatment plan.…”
Section: Methodsmentioning
confidence: 99%